Soluble urokinase plasminogen activator receptor (suPAR) as a prognostic marker of mortality in healthy, general and patient populations: protocol for a systematic review and meta-analysis. Issue 7 (19th July 2020) - Petersen, Jens Emil Vang; Kallemose, Thomas; Barton, Karen D; Caspi, Avshalom; Rasmussen, Line Jee Hartmann
Abstract : Introduction: Chronic inflammation is increasingly recognised as a major contributor to disease, disability and ultimately death, but measuring the levels of chronic inflammation remains non-canonised, making it difficult to relate chronic inflammation and mortality. Soluble urokinase plasminogen activator receptor (suPAR), an emerging biomarker of chronic inflammation, has been proposed as a prognostic biomarker associated with future incidence of chronic disease and mortality in general as well as patient populations. Proper prognostic biomarkers are important as they can help improve risk stratification in clinical settings and provide guidance in treatment or lifestyle decisions as well as in the design of randomised trials. Here, we wish to summarise the evidence about the overall association of the biomarker suPAR with mortality in healthy, general and patient populations across diseases. Methods and analysis: The search will be conducted using Medline, Embase and Scopus databases from their inception to 03 June 2020 to identify studies investigating 'suPAR' and 'mortality'. Observational studies and control groups from intervention studies written in English or Danish will be included. The 'Quality In Prognosis Studies' tool will be used to assess the risk of bias for the studies included. Unadjusted and adjusted mortality outcome measures (eg, risk ratios, ORs, HRs) with 95% CIs will be extracted for healthy individuals, general and patient populations. The primary outcome is all-cause mortality within any given follow-up. Subgroup analyses will be performed based on time of outcome, cause of death, population type, adjustments for conventional risk factors and inflammation markers. Ethics and dissemination: This systematic review will synthesise evidence on the use of suPAR as a prognostic marker for mortality. The results will be disseminated by publication in a peer-reviewed journal. Data used will be obtained from published studies, and ethics approval is therefore not necessary for this systematic review. Trial registration number PROSPERO: CRD42020167401.